Lectins: Function, structure, biological properties andpotential applications - Santos, Andréa F. S. (2014)
Lectins are a special class of proteins widely distributed in nature, which selectively recognize and reversibly bind to carbohydrates and glycoconjugates through their binding sites. These proteins, which can be detected through haemagglutination assays, interact with different carbohydrates present in cell surfaces. Lectins are generally classified according to their structure, specificity for carbohydrates and species location. Depending on their properties and distribution in tissues, lectins can play important physiological roles. The characteristic property of lectins to recognize other molecules in a distinct way makes it relevant in research involving purification, structural analysis, in vitro/in vivo applications of these macromolecules and biotechnological uses in different areas such as molecular and cell biology, immunology, pharmacology, medicine, clinical analysis, nanotechnology as well as in systems for drug release. Lectins can be used for analysis of structure and physiology of cells, tissues and pathogenic microorganisms. In agriculture, these proteins are used as insecticidal agents. Lectins have already been shown to exhibit different biological activities and effects, such as mitogenic and antiproliferative activities on cell lines of human cancer, inhibition of bacterial and fungal growth, action as promoting agents in cell aggregation, immunomodulatory activities and toxic effects. These proteins are promising as drugs for treatment and in diagnosis of human diseases; they are important tools in cytochemistry, histochemistry and immunohistochemistry and are also useful in forensic medicine. In summary, this review provides an overview of lectin research, with focus on physiological functions, structural performance, classification, potential biotechnological properties and applications.